ENCOUNTER, TRANSFORMATION, AND AGENCY IN A CONNECTED WORLD - Broomhall, Susan, author. ([London])
1 online resource
Keywords: Analysing a series of narratives that described women who transformed the worlds they lived in, this book introduces students and scholars to the lives of the women of Joseon Korea 1550-1700. Exploring their interactions bothat home and abroad, this book shows how the agency of these women reached far across the globe The narratives explored here appeared in a wide range of written, visual and material forms, from woodcuts and printed texts, letters, journals, and chronicles to inscriptions on monuments, and were produced by Joseon's elite officials, grieving families, Japanese civic administrators, Jesuit missionaries, local historians of the Japanese ceramic industry, and men of the Dutch East India Company. The women whose voices, lives, and actions were presented in these texts lived duringa time when Joseon Korea was undergoing substantial social, political, and cultural changes. Their works described women's capacity to transform, in ways large and small, themselves, their families, and society around them. Interest in such women was not limited to a readership within the kingdom alone in this period but was reported across transnational networks to a global audience, from Japan to Europe, carrying messages about Korean women's agency far and wide. Encounter, Transformation, and Agency in a Connected World: Narratives of Korean Women, 1550-1700 is essential reading for students and scholars interested in the history of Joseon Korea and Asia and the history of women in the early modern period more broadly.